Towards a circular economy in the aviation sector using eco-composites for interior and secondary structures. Results and recommendations from the EU/China project ECO-COMPASS - Bachmann, Jens; Yi, XiaoSu; Tserpes, Konstantinos; Sguazzo, Carmen; Barbu, Lucia Gratiela; Tse, Barbara; Soutis, Constantinos; Ramón, Eric; Linuesa, Hector; Bechtel, Stéphane (MDPI AG, 2021)
Fiber reinforced polymers play a crucial role as enablers of lightweight and high performing structures to increase efficiency in aviation. However, the ever-increasing awareness for the environmental impacts has led to a growing interest in bio-based and recycled ‘eco-composites’ as substitutes for the conventional synthetic con-stituents. Recently, the international collaboration of Chinese and European partners in the ECO-COMPASS pro-ject provided an assessment of different eco-materials and technologies for their potential application in aircraft interior and secondary composite structures. This project summary reports the main findings of the ECO-COM-PASS project and gives an outlook to the next steps necessary for introducing eco-composites as an alternative solution to fulfill the CLEAN SKY target.